Cyperaceae tribe Cyperae : phylogenetic relationships and evolutionary patterns of diagnostic characters - Dludlu, Meshack N (Department of Biological Sciences, 2017)
Phylogenetic relationships in Cyperus and allied genera in the tribe Cypereae (family Cyperaceae) have been reconstructed using parsimony and Bayesian analyses of a combined data matrix, which consisted of plastid DNA (rbcL, trnL-F intergenic spacer, and rps16), nuclear ribosomal DNA (internal transcribed spacer ITS) sequences and morphological data. From both analyses, tribe Cypereae were resolved into a very strongly supported clade (Posterior probability =98%; Bootstrap= 100%) characterised by the Cyperus-type of embryo and the absence of perianth segments. Cyperus sensu stricto is not monophyletic as currently resolved as several cyperoid genera are embedded within it. The Cyperoid clade splits into two distinct clades which are diagnosed by the Eucyperoid (C₃) and Chlorocyperoid (C₄) anatomy. The evolution of key morphological characters used to diagnose genera is discussed and genera whose classification needs to be revisited are highlighted.